PENGARUH KNOWLEDGE LEADERSHIP, KOMUNIKASI, DAN MOTIVASI TERHADAP KINERJA KARYAWAN PADA PT VALADOO INDONESIA - Rakhmawati Oktavianna (JIMFE (Jurnal Ilmiah Manajemen Fakultas Ekonomi), 2019)
Employee performance is considered important for organizations due to the success of an organization influenced by it. Job performance or achievement is the job result which accomplished by an employee in performing tasks according to the responsibility given to him. A common problem that must be considered in the company is related with job performance. Without good employee’s performance at PT Valadoo Indonesia, its excellence is not going to happen. One of the factors that can be used to improve the employee’s performance is knowledge leadership, communication and motivation. Leaders who have a good knowledge and experience will be able to improve the performance of employees in achieving the company's vision and mission. In carrying out the work, the employee can not be separated from communication with fellow co-workers, the boss and the subordinate. Good communication can be an appropriate means to improve employee performance. In addition to communication, it is also necessary if the motivation for employees with high work motivation usually has a peak performance. Therefore, the research aims to know what is the effect of knowledge of leadership, communication, and motivation on employee performance at PT Valadoo Indonesia either partially or simultaneously. The aim of the study is also  to identify and analyze the effect of knowledge of leadership, communication, and motivation on PT Valadoo Indonesia employee performance. The theory used in this study is theories of human resource management, especially those related to knowledge leadership, communication, motivation, and performance of employees. Population  used in this study is the employee of PT Valadoo Indonesia. Sampling technique used is simple random sampling. Method of data collection is using questionnaire data analysis that is Structural Equation Modeling (SEM) of Lisrel 8.7.